L’effet-blog en littérature. Sur L’Autofictif d’Éric Chevillard et Tumulte de François Bon - Marie-Ève Thérenty (Itinéraires)
This article deals with the “blog effect” in literature, from Chevillard’s L’Autofictif and Bon’s Tumulte. What does remain of the initial blog, beyond the subjective way of writing, when the texts are published? Chevillard activates in the blog its characteristics as a media (fragmentation, everyday life, irony) and doing so, he is not unlike writers-journalists as Allais or Fénéon. Bon activates the support effect in all its potentialities. For both of them, a large part of the literaricy is located in what exceeds the blog, especially in the project of transfer from a blog to a book.